PENGABDIAN PADA MASYARAKAT UNTUK PEMBERDAYAAN PEREMPUAN KELURAHAN SAMBONGPARI MELALUI PELATIHAN PEMBUATAN DAN PEMASARAN RENGGINANG - Dedi Karmana; Kartijo; Silvy Kartikasari; Nenden Hendayani; Ahmad Husen; Fauziyyah Sahar; Nelli Novyarni; Cikal Rosyayuda; Muhammad Rofi' Alqulyubi; Soni Tri Senjaya; Muhamad Abdul Azis; Rani Nuraeni (Adiba Aisha Amira, 2025)
Rengginang Crackers are a food made from glutinous rice where the glutinous rice grains are combined and become a crunchy cracker-like food. In community service activities, training in making rengginang with plants as food coloring will provide knowledge and skills to women in the village in processing local ingredients into products that have added value and high economic value. The stages of this training start from the selection of materials, processing techniques, the coloring process, and good packaging. Another important aspect, namely the marketing aspect, is provided with the aim of village women being able to sell rengginang products with more effective marketing strategies. The benefits of this community service activity are aimed at female MSMEs and youth in the environment of babakan cikurubuk, Tasikmalaya Regency. Business actors in babakan cikurubuk, Tasikmalaya Regency, especially women, are currently utilizing agricultural products as business products. Business actors in babakan cikurubuk, Tasikmalaya City, especially women, can also make rengginang from sweet potatoes, glutinous rice, and rice as well as food coloring from plants. This activity benefits the village community, and the community service also serves as a catalyst for students to improve their organizational skills and participate in a Community Service Program (PKM) under the guidance of a supervising lecturer. Evaluation results for MSME participants indicate that 95 percent have grasped the material presented in the training. This demonstrates that participants understand how to empower rengginang production.